The frequency of the predominant Jewish mutations in BRCA1 and BRCA2 in unselected Ashkenazi colorectal cancer patients - Chen-Shtoyerman, R (Nature Publishing Group, 2001)
It is presently unclear whether carriers of BRCA1 mutations have an increased risk for colorectal cancer (CRC). To gain insight into this issue, 225 unselected Ashkenazi Jewish CRC patients were tested for the presence of the three common Jewish BRCA1/2 germline mutations: 185delAG and 5382insC (BRCA1) and 6174delT (BRCA2). A total of four carriers was found (4/225, 1.78%). This frequency is similar to the estimated normal Ashkenazi population frequency, thus suggesting that these specific mutations do not contribute to CRC predisposition.© 2001 Cancer Research Campaign http://www.bjcancer.com